The Potential of Geodesign for the Optimization of Land Use in the Perspective of Sustainability: Case Study of the Metropolitan Region of Campinas - Pancher, Andréia Medinilha [UNESP]; de Sá, Ana Isabel; Costa, Marcelo [UNESP]; Aguiar, Tiago Oyan [UNESP] (Springer Nature, 2021)
The main objective of this article is to present and discuss the experience of a Geodesign workshop aimed at the Metropolitan Region of Campinas, SP. It was intended to debate the potential of the Geodesign method to reflect on the characteristics of the territory and propose alternatives for the proper use and occupation of land in the region from the perspective of sustainability. The workshop offered support for the participants to co-create alternatives for the sustainable planning of the territory and to develop the potential of the area. Its main characteristic was the elaboration of proposals based on the sustainability triad: Environmental, Economic and Social. The results showed that the methodology favors the preparation of proposals for adequate land use, allowing for an evolutionary process of co-creation of ideas, as the activities were developed in an evolutionary way, that is, the proposals were created for the 2035 and 2050 scenarios, no innovations, few innovations and many innovations. After the preparation and presentation of the proposals, the groups analyzed them for the 2050 scenario, showing that this step is essential for the critical analysis of the ideas, allowing to verify which systems were fully contemplated, which were moderately covered and which were not adequately covered. Thus, it is suggested that the evaluation stage precedes the adequacy and finalization of the proposals.
Keywords: Co-creation; Geodesign; Metropolitan regions; Territorial planning